Factors influencing university students' academic program preferences: An analysis of Albanian data - Flora Zyberaj; Redona Dudushi; Alketa Dervishi; Marsela Robo; Valbona Bezhani; Etleva Smakaj; Risida Gjonej; Zahide Sulejmani; Ela Ali; Erjona Abazaj (Acta Psychologica)
Adolescents' decisions about academic program preferences are becoming increasingly significant, as they are crucial to realizing their dream of developing into unique individuals with secure careers. The study aimed to evaluate the psycho-emotional and social elements that affect students' decision to select a university preference and how their self-reports after starting their studies in that field are used to assess that choice. A questionnaire with four groups of factors together with demographic data was investigated among 356 students to determine their importance related to academic program preferences at the university. A rigorous evaluation was conducted to ascertain its validity and reliability, which was estimated at 89 % and α = 87 %. All constructs exhibited “good” internal consistency. The results of the study indicate that social and emotional supports are significant predictors of students' academic program preferences. In addition, it was determined that parents had the most significant impact on their children's academic preferences, followed by the children's intrinsic motivation and individual interest in the field of study. Significant differences were found when we evaluated the relationship between demographic factors and dependent variables with the importance of factors selected in this study. In conclusion, the findings suggest that social and emotional factors exert an influence on the academic preferences of students. Furthermore, it is evident that their educational trajectory is shaped by external factors, particularly those exerted by their parents. In-depth qualitative and quantitative research should also be carried out to thoroughly assess all the variables that influence academic preferences.